2019
DOI: 10.5194/bg-16-3233-2019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of deep soil carbon – insights from <sup>14</sup>C time series across a climatic gradient

Abstract: Quantitative constraints on soil organic matter (SOM) dynamics are essential for comprehensive understanding of the terrestrial carbon cycle. Deep soil carbon is of particular interest as it represents large stocks and its turnover times remain highly uncertain. In this study, SOM dynamics in both the top and deep soil across a climatic (average temperature ∼ 1-9 • C) gradient are determined using time-series (∼ 20 years) 14 C data from bulk soil and waterextractable organic carbon (WEOC). Analytical measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…We also found that the relative importance of MAP‐PET in predicting SOC remained relatively constant with depth (Figure 6a), consistent with the finding of van der Voort et al. (2019). The relative importance of MAT as a predictor of SOC even increased with depth, contrasting with previous studies that did not include geochemical variables (Gray et al., 2016; Jobbágy & Jackson, 2000).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that the relative importance of MAP‐PET in predicting SOC remained relatively constant with depth (Figure 6a), consistent with the finding of van der Voort et al. (2019). The relative importance of MAT as a predictor of SOC even increased with depth, contrasting with previous studies that did not include geochemical variables (Gray et al., 2016; Jobbágy & Jackson, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, SOC at depth may be protected from biological attack because of spatial isolation from decomposers, decreased labile C supply, and/or differences in temperature or moisture relative to surface horizons (Schmidt et al., 2011). The relative importance of precipitation for predicting SOC may remain consistent (van der Voort et al., 2019) or decrease (Jobbágy & Jackson, 2000) with depth, while the importance of temperature often decreases with depth (Gray et al., 2016; Jobbágy & Jackson, 2000). However, geographically comprehensive research on controls over deep SOC versus surface SOC remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term persistence of GDGTs could arise from their stabilization by soil minerals at greater soil depths. The amphiphilic nature of lipids, such as GDGTs with both polar and hydrophobic components, promotes the association with mineral surfaces and therefore may afford physical protection from degradation (Jandl et al, 2004;Kleber et al, 2007;von Lützow et al, 2008;Van der Voort et al, 2017). By comparison, in surface soils with high organic matter contents and less availability of reactive mineral surfaces, GDGTs are continuously produced and degraded, which results in a younger mean radiocarbon age and evidence for turnover on decadal timescales (Weijers et al, 2010).…”
Section: Radiocarbon Constraints On the Origin And Turnover Of Gdgts In Soilsmentioning
confidence: 99%
“…There are two primary mechanisms by which low Δ 14 C values could be observed in HF in our study: (1) presence of shale-derived OC and (2) unusually long aging of plant or microbial-derived OC through chemical alteration and mineral protection. Rock-derived OC has been implicated in low Δ 14 C values observed in areas where OC-rich (e.g., shale) bedrock is present, including in soils (Hemingway et al, 2018;Longbottom & Hockaday, 2019;van der Voort et al, 2019), lake sediments (Blattmann et al, 2019;Vonk et al, 2016), and riverine suspended particulate matter (Kao & Liu, 1996;Vonk et al, 2016). Gurwick et al (2008) observed 14 C ages of 10,650-17,050 years B.P.…”
Section: Evidence For Shale-derived Oc In Mineral-associated Fractionsmentioning
confidence: 99%